Psychological Capital and Innovative Work Behavior in Small and Medium Entrepreneurs - Ceria Hermina (Psikostudia : Jurnal Psikologi, 2024)
Small and medium entrepreneurs (SMEs) often face challenges in running their businesses. Not a few SMEs have gone bankrupt due to the lack of innovation in running and developing their businesses. This study aims to determine the role of psychological capital in innovative work behaviors of SMEs entrepreneurs. The research method is a quantitative non-experimental, correlational, and cross-sectional design and using simple linear regression analysis. The study included 70 SMEs entrepreneurs from Banjarmasin, South Kalimantan. The results of the analysis show that psychological capital plays a role in increasing the innovative work behavior of SMEs entrepreneurs. The implication of this research is to increase the psychological capital of SMEs entrepreneurs so that they can create innovations in running their businesses and can compete internationally.Pelaku UMKM sering kali menghadapi tantangan dalam menjalankan usahanya. Tidak sedikit UMKM yang bangkrut dikarenakan minimnya inovasi dalam menjalankan dan mengembangkan usahanya. Penelitian ini bertujuan untuk mengetahui peran modal psikologis terhadap perilaku kerja inovatif pelaku UMKM. Metode penelitian yang digunakan adalah kuantitatif non eksperimen dengan desain korelasional dan cross-sectional serta menggunakan analisis regresi linear sederhana. Responden penelitian adalah pelaku UMKM di Banjarmasin, Kalimantan Selatan yang berjumlah 70 orang. Hasil analisis menunjukkan bahwa perilaku kerja inovatif pelaku UMKM dapat ditingkatkan melalui modal psikologis. Implikasi penelitian ini adalah meningkatkan modal psikologis para pelaku UMKM sehingga mereka mampu menciptakan inovasi-inovasi dalam menjalankan usahanya dan bisa bersaing secara internasional.